2005
DOI: 10.1590/s1519-566x2005000300015
|View full text |Cite
|
Sign up to set email alerts
|

Dinámica poblacional y fenología del salivazo de los pastos Zulia carbonaria (Lallemand) (Homoptera: Cercopidae) en el valle geográfico del río Cauca, Colombia

Abstract: -We studied the population fluctuation of nymphs, adults, eggs and natural enemies of the spittlebug Zulia carbonaria(Lallemand) (Homoptera: Cercopidae) associated with Brachiaria dictyoneura pastures of the Cauca River Valley, Colombia. Our objective was to describe spittlebug phenology under seasonal conditions of bimodal precipitation (March-May and September-November). Weekly, over two years, populations of spittlebugs and certain natural enemies were quantified using a sweep net (adults) and counts of nym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
1
7
0
6
Order By: Relevance
“…Thus, in humid zones, the insects achieve up to 6 generations per year (Sotelo and Cardona, 2001). This seasonal dynamic was reported for Zulia carbonaria (Lallemand, 1924) and Aeneolamia reducta (Lallemand, 1924) in colombian pasture systems for bimodal and monomodal rainfall patterns respectively (Peck et al, 2002;Castro et al, 2005), and Aeneolamia contigua (Walker, 1851) in sugarcane crops in Mexico, having a higher abundance of nymphs and adults after the rainy season started (Olán-Hernández et al, 2016). Additionally, Herrera-Huerta et al (2004) found that high humidity rates increase the egg hatching and survival rate of Aeneolamia postica (Walker, 1858) collected from sugarcane in Mexico in laboratory conditions.…”
Section: Population Dynamicssupporting
confidence: 56%
“…Thus, in humid zones, the insects achieve up to 6 generations per year (Sotelo and Cardona, 2001). This seasonal dynamic was reported for Zulia carbonaria (Lallemand, 1924) and Aeneolamia reducta (Lallemand, 1924) in colombian pasture systems for bimodal and monomodal rainfall patterns respectively (Peck et al, 2002;Castro et al, 2005), and Aeneolamia contigua (Walker, 1851) in sugarcane crops in Mexico, having a higher abundance of nymphs and adults after the rainy season started (Olán-Hernández et al, 2016). Additionally, Herrera-Huerta et al (2004) found that high humidity rates increase the egg hatching and survival rate of Aeneolamia postica (Walker, 1858) collected from sugarcane in Mexico in laboratory conditions.…”
Section: Population Dynamicssupporting
confidence: 56%
“…On the other hand, a significant correlation between rainfall and the number of A. varia and D. flavopicta nymphs has been demonstrated ( Melo et al 1984 , Figueredo et al 2012 ); however, no correlation has been suggested between precipitation and the number of A. varia adults in sugarcane crops. Thus, apart from the abiotic factors mentioned above, the presence of nymphs could account for the increase in adults in the field ( Castro et al 2005 ). In sugarcane crops approximately 6 mo old, the abundant foliar area increases humidity, which along with the development of secondary roots at the soil surface level affects the development and abundance of spittlebug nymphs.…”
Section: Resultsmentioning
confidence: 99%
“…However, advances in the development of an efficient management program have been limited due to insufficient knowledge of the effects of climate on population ecology in a sugarcane agroecosystem ( Figueredo et al 2013 ). Additionally, this cercopid species has developed a crucial mechanism to overcome climate variations through the production of diapause eggs, which are able to synchronize their life cycle with the rainy season ( Fontes et al 1995 , Castro et al 2005 ). Thus, considering the ability of cercopid species to adapt to their environment, several studies predicting population fluctuations have been carried out.…”
mentioning
confidence: 99%
“…The egg viability was checked daily. Eggs were classified according to the criteria adopted by Castro et al ( 2005 ), in which nymphs whose eggs hatch during the first 30 days are non-diapausing and those that hatch after this period are diapausing. The number of normal, diapausing, and non-viable eggs, and the total average number of eggs laid per female, were recorded each day.…”
Section: Methodsmentioning
confidence: 99%